Characterisation of anticancer properties of a novel and naturally isolated bisindole alkaloid, conofolidine - Al-Hayali, Mohammed Zuhair Khaleel (2018)
Natural products play a pivotal role in the exploration of new cancer therapies of which the plant kingdom is a substantial source. Conofolidine is a novel bisindole alkaloid isolated from Malayan plant Tabernaemontana Corymbosa and belongs to the family of the known vinca alkaloid conophylline. To our knowledge, no published work existed at the time of commencement of this project. Herein, we report for the first time recognition of conofolidine’s exceptional anticancer activity, from a panel of Malayan bisindoles (namely leucophyllidine, bipleiophylline and alstonia macroline-sarpagine bisindoles) that were indiscriminately screened against various human-derived carcinoma cell lines. Preliminary data showed that conofolidine exerted remarkable inhibition of cell proliferation and colony formation of cancer cells (e.g. GI50 = 0.054 and IC50 < 0.1 μM in MCF-7) through either induction of apoptosis or senescence. Apoptosis was confirmed by accumulation of cleaved PARP and activation of caspases 3/7. Alternatively, increased β-galactosidase positive cells accompanied by transformation of cell shape to spindle like with enlarged cell size ascertained senescence induction. G1 cell cycle arrest and S-phase depletion were observed in the majority of tested cell lines. These cell cycle perturbations were confirmed by decreased expression of positive regulators (CDK2, cyclin A2 and c-Myc) and increased expression of CDK inhibitors p21WAF1/CIP1, p27KIP1 and p15INK4b. Conofolidine caused several aberrant mitotic phenotypes exemplified by multi-nucleation, mitotic slippage, changed polarity, membrane blebbing and DNA fragmentation. Compromised DNA integrity was confirmed by increased γ-H2AX foci and/or level indicating DNA double strand breaks. Conofolidine increased ROS production, which partly contributed to DNA damage, apoptosis- and senescence-induction. A proteomic study conducted following exposure of HT-29 cells to conofolidine (72 h; 0.602 µM) corroborated ROS generation by the increased expression of several ROS scavengers e.g. NQO1. Phospho-proteomics analyses revealed significant suppression of p-EGFR, p-Akt, p-ERK and p-STAT signal transduction. Such suppression caused c-Myc destabilisation with consequent eliciting of either apoptotic or senescent phenotypes. The variation in the basal phosphorylation levels of these signalling proteins in the different tested cell lines determined their fates. Additionally conofolidine down-regulated mutant-p53 at transcription, expression and post-translational levels in mutant-p53 (R273H) cell lines which could partly contribute to its suppressive actions on signalling pathways and cell cycle. Proteomic analyses showed decreased expressions of MCM (2-7) including MCM4 through which mutant-p53 (R273H) could drive initiation of DNA replication. Conofolidine’s ability to suppress MCM family (together with ROS production) provides an additional mechanism for conofolidine to induce DNA damage and genomic instability. Taken together, we present conofolidine in this study as potential anticancer candidate and provide mechanistic insight to its molecular targets and pathways, which encourage further future work.